Evaluation of symmetric flying capacitor multilevel inverter for grid-connected application. (February 2020) - Humayun, Muhammad; Khan, Muhammad Mansoor; Muhammad, Ali; Xu, Jianming; Zhang, Weidong
Highlights: Comparative study of the flying capacitor multi-cells topologies based on output voltage levels with number of components used in an inverter for STATCOM application. Proposed control strategy forsfc topology. Active and pasive component losses are discussed. Simulated and experimental results are presented to shows the effectiveness of proposed topology and its control. Abstract: Grid voltage regulation and reactive power control have been revolutionized by high-voltage high-power multilevel inverters (mli s) topologies. The implementation of such inverters instatcom application make it more feasible due to its multilevel output voltage, low harmonics, high modularity, and high-power quality. However, these topologies require more number of devices which adversely affect the overall system's size, cost, and increase the control complexity. Recently, a packedu -cell (asymmetric flying capacitor) topology has been reported in literature with more output voltage levels using minimum number of components count. The conventional packedu -cellmli utilizesdc -sources to fedac loads. In this paper, a symmetric flying capacitor (sfc )mli is introduced for grid-connected application. The proposed topology is suitable for medium voltage high-power grid-connected applications due to low voltage rating of switches. Thesfc-mli utilizesdc -capacitors instead ofdc -sources, therefore the inverter suffers from voltage imbalance problem. The voltage imbalance is due to non-ideal devices, asymmetric switching losses, and/or non-linear loads. Hence the capacitor balancing is relatively challenging task due to availability of limited number of redundant switching states. A multi-stage feedback control method is proposed with level-shifted (ls )pwm technique to address this issue. Furthermore, a comprehensive comparison in terms of redundant switching states and voltage rating of switches, has been carried out to highlight the superiority of the proposed topology over the existing packedu -cell topologies. In addition, the devices count, and components losses are studied. Finally, simulated and experimental results for different scenario are presented to validate the proposed topology and its control technique.